Urgensi Pengendalian Pemecahan Sertifikat Tanah Sawah untuk Perlindungan Lahan Pertanian Berkelanjutan - Silviana Desi Safitri (Notaire, 2026)
The subdivision of land certificates for paddy fields in Indonesian agrarian law practice is part of land administration services aimed at providing legal certainty over land rights. However, in its implementation, this practice has the potential to cause fragmentation of agricultural land, which may reduce agricultural productivity and accelerate land-use conversion. This study aims to analyze the legal regulation of land certificate subdivision for paddy fields within the Indonesian agrarian legal system and to examine the urgency of its control in the context of sustainable agricultural land protection. The research method used is normative legal research with statutory and conceptual approaches. The findings show that the regulation of land certificate subdivision does not explicitly provide strict limitations oriented toward agricultural land protection, resulting in normative gaps and disharmony between land administration policies and agricultural land protection policies. Furthermore, empirical conditions indicate that land fragmentation through certificate subdivision contributes to the acceleration of agricultural land conversion, as observed in several regions such as Bali, Klaten, and Lampung Selatan. Therefore, legal reconstruction is required through strengthening regulations governing the limitation of paddy field certificate subdivision and integrating land administration policies with sustainable agricultural land protection. Consequently, controlling land certificate subdivision is an essential legal instrument to ensure the sustainability of agricultural land and to support national food security.